2018
DOI: 10.1155/2018/7161592
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Ameliorates Acute Pancreatitis in Mice via Inhibition of Oxidative Stress and Modulation of the Nrf2/HO‐1 Pathway

Abstract: Oxidative stress plays a crucial role in the pathogenesis of acute pancreatitis (AP). Isoliquiritigenin (ISL) is a flavonoid monomer with confirmed antioxidant activity. However, the specific effects of ISL on AP have not been determined. In this study, we aimed to investigate the protective effect of ISL on AP using two mouse models. In the caerulein-induced mild acute pancreatitis (MAP) model, dynamic changes in oxidative stress injury of the pancreatic tissue were observed after AP onset. We found that ISL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(104 citation statements)
references
References 41 publications
(43 reference statements)
11
92
0
1
Order By: Relevance
“…Studies have indicated that oxidative stress and the related production of reactive oxygen species (ROS) play a major role in pancreatic acinar cell injury in AP [12,13]. Moreover, many studies suggest that antioxidant treatment can effectively reduce pancreatic tissue damage and inflammatory response in mice of AP, such as carbon monoxide-bound hemoglobin vesicle [14], coenzyme Q10 [15], and isoliquiritigenin we reported earlier [16]. However, it is far away from the clinical application.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Studies have indicated that oxidative stress and the related production of reactive oxygen species (ROS) play a major role in pancreatic acinar cell injury in AP [12,13]. Moreover, many studies suggest that antioxidant treatment can effectively reduce pancreatic tissue damage and inflammatory response in mice of AP, such as carbon monoxide-bound hemoglobin vesicle [14], coenzyme Q10 [15], and isoliquiritigenin we reported earlier [16]. However, it is far away from the clinical application.…”
Section: Introductionmentioning
confidence: 90%
“…injection of caerulein (200 μg/kg, 10 times at one-hour intervals; Cat. Pep03263, Nanjing Peptide Co. Ltd., Nanjing, China) [16,17]. Mice were randomized into five groups: vehicle, caerulein, caerulein+low-dose TSA (5 mg/kg), caerulein+ medium-dose TSA (25 mg/kg), and caerulein+high-dose TSA (50 mg/kg).…”
Section: Mild Ap Model Induced By Caeruleinmentioning
confidence: 99%
See 3 more Smart Citations